The German spatial poverty divide: poorly endowed or bad luck? - Carsten Schröder
We study inter-temporal changes in poverty for Germany from year 1978 to 2003, and we employ the bootstrap method to test for statistical significance of results. All results are decomposed by household type and region. Poverty estimates are particularly high for single parents. Most striking, however, is the poverty divide between the old and newly-formed German Federal States, with poverty being significantly higher in the latter. We conduct a nonlinear Oaxaca-Blinder decomposition to quantify the separate contribution of regional differences in households’ characteristics to the probability of being poor.Poverty, decomposition, expenditure patterns, necessities, Oaxaca-Blinder decomposition, bootstrap, equivalence scale.